Crafting relations and feminist practices of access - Mudde, Anna E. (Journal of global ethics, 2022)
In this paper, I explore the terrain of craft knowing as an area of expansion for feminist relational theory toward materials, instruments, and design work. I argue that an un(der)-developed attention to craft marginalizes forms of deep knowledge and relational practice. A lens critically oriented to craft affirms the importance of paying attention to how bodies and materials become-together, especially in sites that are usually overlooked, undervalued, and marginalized. If crafting is inherently relational, then craft training is training to negotiate those relations, and attending to craft is a way of understanding such relations and appreciating the knowledges they express. By attending to craft, one moves into a space of being with others where what we might have been trained to perceive as ‘problems’ are just lived realities, and our bodily, practiced responses to them show up as indications of our tendencies and desires. That attention can, I suggest, be leveraged toward greater solidarity practices, including those of accessibility.